Kontrola a kalibrace obráběcích a souřadnicových měřících strojů - Žák, František (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Tato bakalářská práce se zabývá rešerší kontroly a kalibrace obráběcích a souřadnicových měřících strojů používaných v mnoha různých odvětvích průmyslu. Hlavními body této práce je představení různých měřicích postupů dle norem, kalibračních postupů a jejich uplatnění.

This is a bachelor´s thesis concerning the retrieval of monitoring and calibration of machine tools and coordinate measuring machines, used in many different industries. The main points of the work is introduction to different measurement procedures according to standards, calibration procedures and their application.
Monitoring and calibration of machine tools and coordinate measuring machines
Keywords: Měření; kalibrace; kontrola; osy; souřadnice; normy; Measuring; calibration; control; axes; coordinates; standards